Digital information strategies - Baker, David 1952-; Evans, Wendy 1968- (Chandos digital information review series., 2016)
This resource provides a summary and summation of key themes, advances, and trends in all aspects of digital information at the present time, exploring the impact of developing technologies on the information world.